2000
DOI: 10.1081/ppt-100100036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Various Acrylates on the Performance of Ethyl Cyanoacrylate Adhesive

Abstract: Polyalkyl 2-cyanoacrylates begin to retropolymerize and deteriorate dramatically at temperatures above 80°C. They bond rapidly to the metal surfaces and readily lose strength even at ambient temperatures. These two drawbacks of the cyanoacrylates have made this class of adhesives unpopular as structural adhesives. Several attempts have been made to increase the thermal stability and the stability of the bond between the metal surfaces by adding chemicals like cyclopentadienoates and anhydrides to the cyanoacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Similar results were obtained by adding 15 wt% of methyl methacrylate (Figure 1). Samatha et al [17] justified the improvement in the thermal stability by a cross-linking of the ECN and the acrylate monomer, and they were more marked in di-acrylates than in mono-acrylates. On the other hand, good storage stability at 25 °C was observed for all ECN+acrylate mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained by adding 15 wt% of methyl methacrylate (Figure 1). Samatha et al [17] justified the improvement in the thermal stability by a cross-linking of the ECN and the acrylate monomer, and they were more marked in di-acrylates than in mono-acrylates. On the other hand, good storage stability at 25 °C was observed for all ECN+acrylate mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…While the influence of the addition of acrylates in the polymerization of cyanoacrylates has been studied in the past, the use of functionalized acrylates has been barely studied. In fact, Samatha et al [17] have demonstrated that the addition of 5 to 20 wt% of 2-hydroxyethyl methacrylate (Figure 1) increased the adhesion of ECN adhesive, due to the cross-linking between the monomer and the functionalized acrylate, involving the hydroxyl group of the acrylate as nucleophile in the reaction. On the other hand, in the patent by Martín-Martínez et al [19] it has been evidenced a reduction in the heat of polymerization of the ECN by adding different amounts (5 to 20 v/v%) of acrylic derivatives such as 6-hydroxyhexyl acrylate (HHA) and alcoxycarbonyl acrylic acid (ECA) (Figure 1), but an important decrease in the adhesion of the ECN/alcoxycarbonyl acrylic acid (20 v/v%) mixture has been also observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of these adhesives has, therefore, increased for many applications. These adhesives are also often used in preference to contact or heat-sealing adhesives [27][28][29][30] . Acrylate copolymers have gained a considerable significance over other various polymeric raw materials because of their excellent properties, such as ageing resistance and light stability, good adhesion to various types of substrates, and ease of application.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(phenyl methacrylates) have higher thermal stability and gain much interest due to their potential industrial uses [8][9][10]. Copolymers of phenyl methacrylate with various acrylates are reported as adhesives for leather to cloth bonding [11][12][13][14][15]. Poly(phenyl methacrylate)s are harder polymers of higher tensile strength and find applications in pressure-sensitive, photo imaging materials [16] and in electrophotographic photoreceptors for offset printing plates [17].…”
Section: Introductionmentioning
confidence: 99%